Industrial training report: Perpustakaan Al-Khawarizmi, Politeknik Merlimau / Syafiqah Ab. Rani - Ab. Rani, Syafiqah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This Industrial Training Report documents the experiences and insights gained during my internship at Perpustakaan Al-Khawarizmi, Politeknik Merlimau Melaka, as part of my Bachelor of Information Science (Hons) in Library Management program. The report outlines the objectives of the internship, detailing the tasks undertaken and the skills acquired throughout the training period. Key contributions from my lecturer, Encik Mohd Ridzuan bin Ibrahim, and industrial training supervisor, Puan Masnida binti Owi Jin@Othman, are acknowledged, highlighting the importance of mentorship in the learning process. Throughout my training, I have engaged with various library operations, which allowed me to enhance my knowledge of library management practices. Additionally, I developed professional competencies that are essential for her future career in the field. This report ultimately reflects my dedication to fulfilling my academic requirements while emphasizing the valuable learning experiences that shaped my practical understanding of library services.